With love... from the age of reason [videorecording (DVD)]. - Samuell, Yann, 1965-; Duchaussoy, Michel, 1938-2012; Marceau, Sophie, 1966-; Csokas, Marton, 1966- (First Run Features, 2010)
An executive at a multinational construction firm, Margaret's regimented lifestyle revolves around meetings, business dinners and pre-scheduled sex with her partner. But when a retired notary delivers a stack of letters written by Margaret when she was seven years old, the successful professional begins to rethink her existence. Moved by the words of herself at seven, Margaret returns to her childhood village to rediscover the fanciful dreams and playful idealism of her youth.